Legal Review of Children as Perpetrators of Criminal Acts of Sexual Intercourse Against Children (Case Study at Cirebon District Court) - Sumiyati, Sumiyati; Mashdurohatun, Anis (Jurnal Hukum Khaira Ummah, 2025)
Abstract. The crime of sexual intercourse committed by a child against a victim of the same age is an extraordinary problem, one of which is seen in the problem of the criminal system for the perpetrator, on the one hand the perpetrator who is a child cannot be subject to criminal penalties like an adult perpetrator because of considerations of mental growth and considerations of the child's future. The type of this thesis research is a type of Normative legal research. Based on the results of the research conducted, it can be seen that the basis for the judge's considerations in deciding the case of a child as a perpetrator of a crime of sexual intercourse with a child in the Cirebon District Court consists of legal considerations used by the judge, namely, proof of the crime committed, whether the act has fulfilled the elements of rape referred to in Article 285 of the Criminal Code, and from all the statements of the witnesses and the explanation of the prosecutor's demands, it can be concluded that all elements of the crime of rape committed by the defendant have been proven. Meanwhile, sociologically in his decision, the judge considered the aggravating factors for the defendant, namely: The actions committed by the defendant were inhumane, because the defendant committed harassment and immoral acts against the victim who was still a minor, especially the defendant also threatened the victim, this caused the victim to be afraid and traumatized to the point that the victim did not want to go to school. Meanwhile, the mitigating factors for the defendant were: the defendant admitted all his actions, although at first the defendant denied it, the defendant also expressed regret for having committed his actions to the victim who was considered his own lover or girlfriend, and the most important thing in the judge's consideration was that the defendant was still classified as a child. Legal consequences of the Judge's Decision in the case of Children as Perpetrators of Sexual Intercourse Against Children at the Cirebon District Court, legally, perpetrators of sexual intercourse with children can also be subject to criminal sanctions as regulated in Article 81 of Law Number 35 of 2014 concerning Child Protection, children who commit sexual intercourse with children can also be subject to criminal sanctions as regulated in Article 285 of the Criminal Code.